Study of introduction prospects of cogeneration technologies in municipal energy of Ukraine - Андрєєв, Сергій Юрійович; Маляренко, Віталій Андрійович; Темнохуд, Інна Олександрівна; Шубенко, Олександр Леонідович; Бабак, Микола Юрійович; Сенецький, Олександр Володимирович (Eastern-European Journal of Enterprise Technologies, 2015)
The analysis of low-power electric generating plants, used in the transition of existing boiler houses into a mini-CHP was conducted. The main comparative characteristics of the RGE and GTP for small electric generating facilities were presented. The forecasts of the Ministry of Housing and Communal Services of Ukraine regarding trends in tariffs for heat, electricity and natural gas in Ukraine were analyzed. The characteristics of the structure, energy equipment and energy efficiency of the ME “Kharkiv heating networks”, based on which the feasibility estimation of cogeneration principles on the example of the boiler house, included in the association were considered. For the selected facility, the feasibility study on its transition into a mini-CHP by installing reciprocating gas engines was carried out. The way the gas price affects the project payback period is shown.